Pendampingan Budidaya Ikan Lele di Desa Sampora Cisauk - Natalia, Christine; Sukwadi, Ronald; Kartawidjaja, Maria Angela; Goenawan, Stephanus Ivan; Uyanto, Stanislaus Suryadi; TIrtaulima, Chelsea Naomi; Asmaralda, Naftalia (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2021)
This community service activity aims to develop entrepreneurship following the village's potential, namely catfish and hydroponic cultivation, often known as 'aquaponics'. One of the residents of Sampora Village, namely Pak Ali, has been engaged in catfish hatchery cultivation for many years and has become a pioneer in developing catfish cultivation to other Sampora villagers. This mentoring activity is an entrepreneurial assistance activity for catfish hatchery for Sampora villagers. The results of this activity are expected to be a productive sustainable entrepreneurship activity.